2011
DOI: 10.1002/nau.21013
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients who regain urinary continence in the first week after acute first‐ever stroke have better prognosis than patients with persistent lower urinary tract dysfunction

Abstract: We confirmed that post-stroke UI is a predictor of greater mortality at 1 week, 6 months and 12 months after stroke. However, patients who regain normal bladder control in the first week have a comparable prognosis as the patients who do not have micturition disturbances following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Wehrberger et al reported a higher risk of cardiovascular disease and stroke events (adjusted hazard ratio 3.82, p  = 0.01) for men with severe LUTS during a mean follow-up period of 6.1 years, after adjusting for age, diabetes, total- and low-density lipoprotein cholesterol in a 10-year follow-up longitudinal analysis, although moderate LUTS do not seem to be a risk factor for cardiovascular disease and stroke (adjusted hazard ratio 0.63, p  = 0.16) [10]. It has also been shown that urinary incontinence is a predictor of an increased risk of mortality and poor functional recovery as well as of post-stroke institutionalization [32]. LUTS was considered a prognostic factor after acute first-ever stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wehrberger et al reported a higher risk of cardiovascular disease and stroke events (adjusted hazard ratio 3.82, p  = 0.01) for men with severe LUTS during a mean follow-up period of 6.1 years, after adjusting for age, diabetes, total- and low-density lipoprotein cholesterol in a 10-year follow-up longitudinal analysis, although moderate LUTS do not seem to be a risk factor for cardiovascular disease and stroke (adjusted hazard ratio 0.63, p  = 0.16) [10]. It has also been shown that urinary incontinence is a predictor of an increased risk of mortality and poor functional recovery as well as of post-stroke institutionalization [32]. LUTS was considered a prognostic factor after acute first-ever stroke.…”
Section: Discussionmentioning
confidence: 99%
“…LUTS was considered a prognostic factor after acute first-ever stroke. Patients who regain normal bladder control in the first week have a prognosis that is comparable to that of patients who do not have micturition disturbances following a stroke [32]. Therefore, the increased economic burden raises the possibility that treating LUTS/OAB at an early stage can both improve patient care and minimize overall use of health-care resources [30].…”
Section: Discussionmentioning
confidence: 99%
“…Die Harninkontinenz ist ein prognostischer Faktor für den Schweregrad des Schlaganfalls und die anschließende Genesung, da mit persistierender Harninkontinenz nach Schlaganfall die Wahrscheinlichkeit von Invalidität und Tod zunimmt [10,54].…”
Section: Funktionsstörungen Des Uht Bei Msaunclassified
“…Both have been reported to be signs of a poor prognosis in patients with stroke. [45] However, these signs were judged in the subacute or chronic phase during hospitalization, and only Nakayama et al . reported the significance of UI on arrival.…”
Section: Introductionmentioning
confidence: 99%
“…reported the significance of UI on arrival. [4611] Moreover, even Nakayama et al . evaluated 32% of the patients with stroke in the subacute phase together with those in the acute phase.…”
Section: Introductionmentioning
confidence: 99%